PERSONAL IDENTITY OF THE CHARACTERS OF G. ROY'S NOVEL "THE ROAD TO PAST ALTAMONT" AND MUSICAL ALBUM “THE OLD MAN AND A CHILD” CREATED ON ITS BASIS (Psychology Travelogs, 2021)
The article analyzes the features of the personal identity of the characters of the novel by the Canadian writer G. Roy’s "The Road to Past Altamont", in particular the second part of "Old Man and Child" and the eponymous music album, created in 2021 based on him. First published in French in 1966, the book's title is lifted from the last story “La Route d'Altamont" is a wonderful old-fashioned coming-of-age-themed 4-group of stories about a young francophone girl - Christine - growing up in lonely, windswept, pioneering Manitoba at the turn of the twentieth century. The subject of the novel penetrates to the heart of a Child’s in-depth world, forming a subtle, yet considerable linkage of impressions, feelings, and relationships. Christine is an autobiographical character, based on G. Roy, and Christine’s memories and responses are, one must therefore speculate, Roy’s. The four stories in this novel are connected, not only by the main character at different points in her life, but also thematically with the exploration of change, aging and how we relate to and understand our elders. The theoretical research question was what kinds of verbal indicators characterize personal identity following the example of G. Roy's novel and the musical album based on it. This empirical study based on the methods of discursive and narrative analysis of the novel "La Route d'Altamont" and the musical album "Le vieillard et l'enfant".It established that verbal markers of personal identity are time (prospective identity) and space (territorial identity). It is proved that personal identity in the novel and music album is presented in the form of an autobiographical narrative, stages of the crisis of personal identity in people of different ages, heredity of generations, options for solving existential problems that are relevant in crisis situations. Acquisition of personal identity is impossible without the choice of individual freedom, without finding one's place in a changing and unpredictable world. The instability of the world encourages freedom of choice, taking responsibility for their actions. G. Roy demonstrates the reflexivity of the characters of the novel through the image of her as "the author of the narrative" and as "his witness". Hence, one of the means of overcoming the identity crisis is reflexivity.
Keywords: narrative; discourse; personal identity; existence; authenticity; identity crisis